SEMANTIC FEATURES OF ENGLISH AVIATION TERMINOLOGY: A LINGUISTIC PERSPECTIVE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
This article examines the semantic features of English aviation terminology, focusing on its precision, systematic organization, and adaptability to technological and operational advancements. Aviation terminology, a vital tool for effective communication in a high-stakes global industry, demonstrates unique semantic properties shaped by its functional and international nature. Through an analysis of its linguistic structure, contextual usage, and global standardization, this study highlights the pivotal role of aviation terminology in ensuring safety, efficiency, and clarity in the aviation sector.